Boar sperm viability, head morphometry, and kinematics during seven-day storage in improvised portable semen shipper - Peña Jr., Santiago T. (Philippine Journal of Science, 2023)
Artificial insemination (AI) is pivotal in sustaining pig reproduction both in back and commercial production systems. With AI, boar-for-hire service boars - which are quite popular in background pig farming in the Philippines - do not have to be transported over long distances. Thus improving efficiency. Biosecurity, and productivity. Once crucial aspect of a successful distance Ai operations is ensuring the timely availability of fresh extended boar semen does stored inappropriate semen cool boxes (15-18 ٥C) to avoid irreversible damage due to cold shock. This study was conducted to objectivity determine the viability, head morphometry, and kinematic performance of boar spermotozoa during storage in [a] an improvised portable semen shipper (sSHPR) as compared to [b] standard semen refrigerator (sSREF) using various extenders at different storage times. Boar semen (n=9) was passed into 80-mL dose (~37.5 x 10⁶ spz/mL) using four difficult extenders: T₀ = 0.9% NaCl solution, T1A = mid-term extender A, T1B = mid-term extender B, and T₂ = long-term extender, and semenquality was monitored at different intervals for up to seven days using the Sperm Class Analyzer CASA systems. Using mixed factor ANOVA, boar system performance generally remained relatively similar between the sREF and sSHPR (p>0.05). Prolonged storage times, however, had a significant effect- particularly toward Days 5 and 7, depending on the extender used. Boar sperm in commercial extenders recorded an average of 78.45 ⩲ 2.23% and 82.85 ⩲ 11.39 % total mobility for sSHPR and sREF on Day 5, respectively. Velocity (VCL, VSL, VAP) and head width also changed over time. The potential to safely store and preserve extended boar semen using an improved portable semen shipper described in this study provides an opportunity to further explore this device as an affordable alternative storage system for extended boar semen for research or AI purposes.